2003
DOI: 10.1046/j.1432-1033.2003.03803.x
|View full text |Cite
|
Sign up to set email alerts
|

The activation of gelsolin by low pH

Abstract: Gelsolin is a multidomain and multifunction protein that nucleates the assembly of filaments and severs them. The activation of gelsolin by calcium is a multistep process involving many calcium binding sites that act to unfold the molecule from a tight structure to a more loose form in which three actin‐binding sites become exposed. Low pH is also known to activate gelsolin, in the absence of calcium and this too results in an unfolding of the molecule. Less is known how pH‐activation occurs but we show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The compact packing of the G2-G6 domains in the structure solved for pH 5 could be due to the close C-tail latch, which "locks" G2/G6 domains and is sensitive only to Ca 2ϩ ions. This observation corroborates with an earlier report that the opening of the C-tail latch, which is one of the first events of Ca 2ϩ -dependent gelsolin activation, might be absent in the pH-mediated activation process (15).…”
Section: Saxs Data Analysis-measured Saxs I(q)supporting
confidence: 93%
See 3 more Smart Citations
“…The compact packing of the G2-G6 domains in the structure solved for pH 5 could be due to the close C-tail latch, which "locks" G2/G6 domains and is sensitive only to Ca 2ϩ ions. This observation corroborates with an earlier report that the opening of the C-tail latch, which is one of the first events of Ca 2ϩ -dependent gelsolin activation, might be absent in the pH-mediated activation process (15).…”
Section: Saxs Data Analysis-measured Saxs I(q)supporting
confidence: 93%
“…Decrement in diffusion coefficient values measured by dynamic light scattering (DLS) supported that lower pH induces opening of the solution structure of gelsolin (13), similar to that seen as a function of increase in Ca 2ϩ ions without changing buffer pH (16). Additionally, biochemical studies supported that low pH leads to a cascade of ion-pair exchanges in gelsolin, which causes disruption of interdomain bonds, but these events were concluded to be distinct from those induced by Ca 2ϩ binding (15). Importantly, one of the first events of Ca 2ϩ -dependent activation, the opening of the C-tail latch (interaction between the C-tail of the G6 and G2 domain), was suggested to be absent in the pH-mediated activation process.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Interestingly, the F-actin depolymerization activity of G1+ is dependent on Ca 2+ and pH, similar to the full-length protein but different from the N-terminal half including domains G1-G3. Previous reports have demonstrated that gelsolin requires no Ca 2+ for in vitro binding to G-actin, nucleating F-actin formation, and severing F-actin filaments at a pH less than 6.01213. According to recent small angle X-ray scattering (SAXS) data, lowering pH from 8 to 5 induces the increase of the gyration radii of gelsolin and G1+ in the absence of Ca 2+ by 9.7% and 11.6%, respectively1014.…”
mentioning
confidence: 99%